Polish-language groups related to autism on Facebook – language analysis of the groups’ descriptions - Góra, Katarzyna (Papers in Linguistics, 2024)
The aim of the study, grounded in semantics and language discourse, is to examine and describe Polish-language Facebook groups related to autism in terms of the key purposes and needs expressed in the descriptions and names of the groups. The pilot study made it possible to indicate the following categories communicated implicitly and explicitly by the creators of the group descriptions: support (emotional and informational), providing safety and acceptance, exchange of experiences, raising awareness (advocacy and development of parental competencies), socialization, therapy and treatment, advertising and offering services, organization of free time. Research on discourse concerning autism in social media is critical in enhancing the understanding of the social context in which autistic people and their relatives function.